Role of steroid 11 beta-hydroxylase and steroid 18-hydroxylase in the biosynthesis of glucocorticoids and mineralocorticoids in humans. - Kawamoto, T (1992)
A gene encoding steroid 18-hydroxylase (P-450C18) was isolated from a human genomic DNA library. It was identified as CYP11B2, which was previously postulated to be a pseudogene or a less active gene closely related to CYP11B1, the gene encoding steroid 11 beta-hydroxylase (P-45011 beta) [Mornet, E., Dupont, J., Vitek, A. & White, P. C. (1989) J. Biol. Chem. 264, 20961-20967]. The nucleotide sequence of the promoter region of the P-450C18 gene is strikingly different from that of the P-45011 beta gene, although the sequences of their exons are 93% identical. The transient expression in Y-1 adrenal tumor cells of CAT constructs with a series of deletion mutants of promoter regions of both genes indicated that the two genes are regulated differently. P-450C18 as expressed in COS-7 cells exhibits steroid 18-hydroxylase activity to catalyze the synthesis of aldosterone and 18-oxocortisol and exhibits steroid 11 beta-hydroxylase activity as well. In contrast, P-45011 beta as expressed in the cultured cells exhibits steroid 11 beta-hydroxylase activity exclusively but fails to catalyze the synthesis of aldosterone and 18-oxocortisol. These results indicate that P-45011 beta and P-450C18 are products of two different genes and that the former participates in the synthesis of glucocorticoids whereas the latter participates in the synthesis of mineralocorticoids in humans.